A follow‐up survey of total intravenous anesthesia usage in children in the U.K. and Ireland. Issue 2 (2nd January 2019) - Goh, Au-Chyun Nicole; Bagshaw, Oliver; Courtman, Simon
Summary: Background: Total intravenous anesthesia usage in children remains relatively unpopular in the UK and Ireland. A postal survey by Hill et al in 2008 indicated that only 26% of Consultants used a propofol infusion at least once a month. Aims: Following an increase in teaching and training opportunities in pediatric total intravenous anesthesia in the UK, we repeated the survey among Consultant members of Association of Paediatric Anaesthetists of Great Britain and Ireland and Society for Intravenous Anaesthesia, to see if this had affected total intravenous anesthesia usage in children and how practice may have changed. Methods: We used an anonymous online survey sent to Association of Paediatric Anaesthetists of Great Britain and Ireland and Society for Intravenous Anaesthesia members. Results: A total of 291 responses were analyzed. Total intravenous anesthesia was the default method of anesthesia in 8% of respondents and a further 46% used total intravenous anesthesia at least monthly. Overall total intravenous anesthesia usage had increased in the past year in 53%. The main indications were malignant hyperthermia susceptibility, and postoperative nausea and vomiting. Ear/nose/throat surgery was the most popular surgical specialty. The main reasons for not using total intravenous anesthesia were that it was too "fiddly" and lack of confidence in the user. Most respondents used propofol in combination with remifentanil. Over 80% used propofol target‐controlled infusion. The potential for propofol‐related infusion syndrome concerned many, with 74% limiting infusion duration as a result. Bispectral Index was not used routinely by the majority of anesthetists. Even though most anesthetists did not use total intravenous anesthesia routinely, 98% felt they would be confident to anesthetize an malignant hyperpyrexia‐positive patient using the technique. Conclusion: This survey has shown that although total intravenous anesthesia is not the default anesthetic technique for most anesthetists, overall usage in children has more than doubled in the past 10 years, with many happy to use it in a wide variety of patients and procedures.